Assistance in the climate village program in increasing food security in Tobek Godang Village - Wasiah Sufi; Trio Saputra; Eka Eka (Universitas Muhammadiyah Magelang, 2022)
The purpose of this program is to improve the Climate Village Program's implementation in Tobek Godang Village, Bina Widya District. The methods of planning, implementation, reflection, and follow-up are used to achieve the objectives of the program. The outcomes of this program can increase community food security on their own. Furthermore, the community's knowledge and ability in the use of land for farming as a solution to meet daily household food needs by cultivating hydroponic plants has increased.